Evaluate the Levels of Serum Eotaxin-1, Myelin Basic Protein, and Some Immunological and Biochemical Markers in Iraqi Patients with Multiple Sclerosis - Sahib, Sarah A. H.; Sulaiman , Ghassan M.; Waheed, Huda J.; Albukhaty, Salim (Iraqi Journal of Science, 2024)
The central nervous system (CNS) disease known as multiple sclerosis (MS) is essentially an inflammatory demyelinating condition with a variety of clinical manifestations and variable histological findings. A number of immunological and biochemical markers may alter MS, which is also characterized as an autoimmune illness. MS patients (n = 100) were divided into two groups: newly diagnosed (n = 42) and patients with ongoing treatments (n = 58). These groups were compared to healthy subjects (n = 55); the mean age ±SD was (30±8.46 years), (37±8.06 years), and (31±8.73 years) for MS newly diagnosed patients, patients with ongoing treatments, and healthy subjects, respectively. Studies for serum levels of eotaxin-1, myelin basic protein (MBP), IL-23, 27, 9, and 37 were measured by the ELISA technique. Eotaxin-1, MBP, IL-23, 27, and alkaline phosphate were significantly higher in all MS patient groups, but for IL-37, there was no significant difference between newly diagnosed patients when compared with patients with ongoing treatment. Weak positive correlations were found between IL-9 and myelin (r = 0.282, p≤0.05) and a weak positive correlation between IL-23 and ALP (r = 0.209, p≤0.05) in MS patients. A receiver operating characteristic (ROC) curve analysis was applied for the parameters eotaxin-1, MBP, IL-23, 27, and alkaline phosphate, which showed a high sensitivity according to the area under the curve. The present results conclude that eotaxin-1, MBP, IL-23, 27, and alkaline phosphate can be used as diagnostic markers for multiple sclerosis.